KETIKA ANAK BERBICARA UNTUK IKLAN DI MEDIA TELEVISI (KOMUNIKOLOGI : Jurnal Ilmiah Ilmu Komunikasi, 2015)
AbstractChildren are orisinal person. The emerge children in advertisement in television is prepared by ideologies and power interest. We saw advertising with constructivition and representative hipereality. Children are described more acticity with identity of background that it is determined by capital owner. There are, children are represented capitalist of ideology in individualist, class, liberty, prosperitu and aliency. Also, capital owner is working in economict Interest to addition capital. Children are represented as healty child, clever, the highest their growing, much eating, life style, richt and the have society. Children are created a consumers and star of child. At there contrary with realy condition. The government by profesion of organization has to such a power rules that media and profesion can to implicated social responbility Keywords: child, advertising, mass media